PHRASAL VERBS IN RICK RIORDAN’S NOVEL THE HAMMER OF THOR: A SYNTACTIC ANALYSIS - Arif Topan, Tegar (Universitas Islam Sumatera Utara (UISU), 2023)
The study about syntax is quite significant because some people may write sentences yet they have no idea the proper structure of grammar. In this study, the writer focuses on syntax which has something to do with phrasal verbs discussed in tree diagram. This study uses The Hammer of Thor novel by Rick Riordan as the data source. The objective of the study is to find out kinds of phrasal verbs in The Hammer of Thor novel and the meaning of those phrasal verbs. This study used qualitative method. There are 33 phrasal verbs found in the novel as the source of data. Those particles which form the phrasal verbs are out, up, for, down, about, back, on, off, into, away, through, from, and over. Based on the data found, the phrasal verbs are different from verb phrases in written form. Furthermore, the tree diagram gives more understanding how phrasal verbs are formed and how to use them syntactically.